Ancient Maya Commerce Multidisciplinary Research at Chunchucmil - Hutson, Scott (University Press of Colorado, 2017)
Nearly two decades of research at Chunchucmil, Yucatan, Mexico documented a thriving city of 40,000 people without the powerful kings and massive temples seen at other Maya centers. What brought people to this area, the driest in the Maya world, and how did they survive? Ancient Maya Commerce provides a pioneering study in economic anthropology, making the strongest case yet that ancient Maya economies were quite complex, containing markets in addition to other forms of exchange. Multiple lines of evidence including household archaeology, regional survey, paleo-ecology and soil chemistry show that Chunchucmil was a major center for both short and long distance trade, integrating the Guatemalan highlands, the Gulf of Mexico and the interior of the northern Maya lowlands. By placing Chunchucmil into the broader context of emerging research at other Maya cities, this book helps reorient our understanding of ancient Maya economies, foregrounding the increasingly important role of commerce.